2015
DOI: 10.1186/s12889-015-1666-9
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in predictors of self-rated health among older adults in Brazil and Chile

Abstract: Background: The determinants of self-rated health (SRH) have been widely investigated to explain social differences and gender differences in health. This study aimed to investigate the gender differences in predictors of SRH among Brazilian and Chilean older adults. Methods: We used two samples of older people: 2052 Brazilian community-dwelling participants (1226 women and 862 men) and 1301 Chilean community-dwelling participants (855 women and 446 men). Sequential logistic regression analysis was used to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
(53 reference statements)
5
20
1
6
Order By: Relevance
“…Methodological details of this study have been reported previously [38,39]. Briefly, the Chilean sample was obtained through a systematic recruitment of individuals aged 60 and over living in the community in Santiago in 1999–2000.…”
Section: Methodsmentioning
confidence: 99%
“…Methodological details of this study have been reported previously [38,39]. Briefly, the Chilean sample was obtained through a systematic recruitment of individuals aged 60 and over living in the community in Santiago in 1999–2000.…”
Section: Methodsmentioning
confidence: 99%
“…População de 40 anos ou mais residente em Cambé, Paraná, Brasil (n = 397). categoria de APNS, no presente estudo, foi definida por ser a forma mais usual verificada na literatura 6,25,26,27,28 . De qualquer modo, não é objetivo deste trabalho realizar comparações exaustivas com a incidência e a prevalência de APNS e APPS observadas em outros estudos.…”
Section: Tabelaunclassified
“…These findings build upon a previous South East Asia Journal of Public Health 2018;8(1):10-16 and negative life events and females to have a higher odd of poor SRH similar to findings in the current study. 50 Evidence-based cost-effective treatments for depression is available. 51 But a diagnosis of depression needs to be made for treatment to be given.…”
Section: Discussionmentioning
confidence: 99%